Ecological engagement as a strategy to investigate the care service of cancer patients (Research, Society and Development, 2020)
The present study aimed to research the work dynamics related to care that health professionals offer to cancer patients during their treatment in the hematology unit of a hospital located in the State of Rio de Janeiro. A single-case qualitative study was carried out based on the theoretical perspective of the Bioecological Model of Human Development. The data were collected and organized according to the directions of the ecological engagement methodology that compiled 70 hours of naturalistic observations and registers in a field diary. 23 health professionals from the hematology unit participated. The analysis followed the principles of the grounded theory. The results revealed axes that demonstrated three different aspects of influence: personal - the subjectivity of the team´s actions; contextual - technical, bureaucratic and humanized protocols; and, relational - patterns of communication, proximal processes and professional practices of the participants. This study highlighted the relevance of ecological engagement as a strategy that reveals categories of analysis that allow the understanding of elements about the dynamics of the work and the involvement of health professionals with their patients. The difference between service and care was emphasized, with the first aspect being more objective and focused on technical, bureaucratic and protocol elements and the second focused on the subjective scope of elements related to resilience in professionals: solidarity, good humor, affection, reciprocity and empathy.